'Hidden in plain sight': Expressing political criticism on Chinese social media. (June 2021) - Wu, Xiaoping; Fitzgerald, Richard
While the proliferation of social media technologies in China has empowered the public with new opportunities for public expression and political engagement in a 'virtual public sphere', Chinese Internet censorship has meant that users have to develop creative ways to engage in political criticism. In a context where both mechanical and human censors are employed, Chinese users have become adept at utilizing the affordances of technology, Chinese language and cultural resources to express their opinions through social media. Drawing upon data from the Chinese microblogging website, Weibo, surrounding the major chemical explosions in 2015 in Tianjin, the study explores three discursive techniques of indirection by Chinese social media users to express political criticism in the context of censorship. The study highlights that through the creative use of quotation, allusion and irony, users challenged the authority's official narratives of the event. The study not only demonstrates the pluralization and dynamics of Chinese online expression, but also points to a better understanding of Chinese censoring as a continuingly evolving interplay between technology and cultural forms and between layers of government and users.